A literature study of ghrita prayoga in treatment of rajyakshma with special reference to charaka samhita - Tule, Charulata; Ketaki Kamat (Ayurline: International Journal of Research in Indian Medicine, 2025)
Aim & Objective: To study the uses of ghrita kalpana in management of rajyakshma with reference to charaka samhita. Observation: It has been noted that numerous ghrita preparations are referenced in the Charak smahita. It is utilized for the shodhan procedures like vaman, virechana, nasya and also as sanshaman chikitsa in the form of external applications (upnah, aalepan, pradeha, pralepa, abhyanga, kawala) as well as internal. It is even utilized as auttarbhaktika sneha, anupaana of some avaleha (in vyadhis like kasa, shwas, swarbheda and parshva shola) and yusha. Furthermore, ghrita is suggested as part of a dietary plan when prepared with juice of meat, dugdha, dashmoola. Various prepared ghrita formulations are described for addressing specific conditions of vyadhi. Conclusion: When treating rajyakshma, the use of ghrita in various formulations and dietary combinations, can prevent the depletion of bala and mamsa in patients, thereby preventing the achikitsya condition associated with rajyakshma vyadhi. Main finding: The advantageous properties of ghrita kalpa suggest that its appropriate application may aid in averting complications associated with rajyakshma. Principal Conclusion: To prevent achikitsya avastha of rajyakshma utilizing / consuming various formulations of ghrita from purva avastha of vyadhi is advisable.